Hypertension Prevalence Based on Three Separate Visits and Its Association With Obesity Among Chinese Children and Adolescents - Zhang, Qian; Yang, Lili; Zhang, Yanqing; Zhao, Min; Liang, Yajun; Xi, Bo (Frontiers in Pediatrics, 2019)
Background: Clinical practice guidelines recommended that hypertension in children and adolescents should be defined based on elevated blood pressure (BP) on at least three separate occasions. Therefore, in the present study, we aimed to estimate the prevalence of hypertension based on three separate visits among Chinese children and adolescents and to examine its relationship with obesity. Methods: A school-based cross-sectional survey was performed in children and adolescents in Jinan, China between September 2012 and September 2014. A total of 7,832 children and adolescents aged 6-17 years were included. Anthropometric data and BP were measured by trained examiners. Elevated BP was defined as BP ≥ 95th percentile for age and sex based on the Chinese reference data. Participants with elevated BP at the first visit underwent a second visit two weeks later, and a third visit was conducted if BP was still high at the second visit. Hypertension was defined as having an elevated BP at all three visits. Obesity was defined in three ways by using body mass index, waist circumference, and waist-to-height ratio. Results: The prevalence of elevated BP decreased substantially across three separate visits, with the prevalence of 17.2%, 8.6% and 4.9%, respectively. Obesity was an independent risk factor for elevated BP during each visit. Based on the body mass index, obesity was associated with higher risk of elevated BP, with the adjusted odds ratios (ORs) and 95% confidence intervals (CIs) of 8.6 (6.8-11.0), 12.5 (9.1-17.3), 14.0 (8.9-22.2), respectively, at the first, second and third visit. The ORs of elevated BP were similar in association with obesity defined by waist circumference or waist-to-height ratio. Conclusions: The prevalence of hypertension based on three visits was ~5% in Chinese children and adolescents. There was a dose-response relationship between obesity and elevated BP across three visits.